Incorporation of CdS nonoparticles from colloidal solution into optically clear ureasilicate matrix with preservation of quantum size effect - Boev, Victor Ivanov (2006)
Nanocomposite materials based on an organic-inorganic ureasilicate matrix with embedded CdS nanoparticles were produced and characterized by optical (UV/Vis), FTIR, secondary ion mass spectroscopy, inductively-coupled plasma optical emission and steady-state photoluminescence measurements. The ureasilicate precursor was obtained by the reaction between silicon alkoxyde modified by isocyanate groups and polyethylene glycol oligomers with amine terminal groups. The final nanocomposites were prepared by introducing a colloidal solution of CdS nanoparticles with various sizes into the ureasilicate precursor followed by gelation of the mixture in the presence of ammonia/water vapours. The reliable preservation of the quantum-size effect of nanoparticles after their incorporation into the ureasilicate matrix was observed in all samples. The obtained materials were optically transparent at visible range, exhibiting high flexibility and long-term stability.